Modelling the Distribution of a Commercial NE-Atlantic Sea Cucumber, Holothuria mammata: Demographic and Abundance Spatio-Temporal Patterns - Félix, Pedro M.; Pombo, Ana; Azevedo e Silva, Francisco; Simões, Tomás; Marques, Tiago A.; Melo, Ricardo; Rocha, Cristina; Sousa, João; Venâncio, Eliana; Costa, José L.; Brito, Ana C. (Frontiers in Marine Science, 2021)
There is an increasing demand for sea cucumbers, for human consumption, mainly from Asian markets and, as a consequence, NE-Atlantic species are now new targets for exploitation and exportation. Holothuria mammata is one of the most valuable species in Europe. However, the lack of historical economic interest in this species in most European countries has also led to a lack of studies concerning biological and ecological aspects on wild populations and this is a major issue for stock management. This study aims to determine the temporal and spatial patterns of distribution of H. mammata, considering its abundance and demographic structure in a NE-Atlantic area, SW Portugal, as a function of environmental conditions. For that, a population from a marine protected area was followed for 1 year at 1.5-month intervals. Throughout the coastal area, six sites were selected and at each sampling campaign three random transects per site and substrate (rock and sand) in which all H. mammata individuals were counted and measured. For each site and survey several environmental parameters of interest, from the water column, the sediment and substrate cover, were also measured. Generalized Linear Models were used to model the spatial and temporal distribution of the species according to environmental conditions, to determine the species’ habitat preferences. The distribution models indicate that abiotic and biotic parameters of the water column are not the main drivers shaping the distribution of H. mammata. The species has a patchy distribution, and its habitat preferences depend on environmental stability, the presence of shelter and habitat complexity, which is more important for smaller, more vulnerable, individuals, while bigger size classes tend to venture more into less stable environments in an opportunistic fashion. The knowledge of these population traits is determinant to develop stock management measures, which are now urgent to prevent the depletion of commercial sea cucumber populations in the NE-Atlantic. Sustainable fisheries policies should be developed and start by considering to delimit fishing areas and periods, considering the species spatial and temporal distribution patterns.